STUDY OF SIEMENS 7UT86 PERCENTAGE DIFFERENTIAL RELAY AS PROTECTION OF 60 MVA POWER TRANSFORMER AT 150 GIS KV DAYEUH KOLOT - Purba, Dian Andreas; Gani, Usman A; Danial, Danial (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Power transformer is a vital equipment in the electric power system that plays an important role in distributing electrical energy from the generator to the load center. Transformers require a protection system that is able to detect an internal or external disturbance with a very fast time to prevent widespread blackouts. Transformer protection generally uses differential relays that require settings in determining their working parameters. On this basis, the authors conducted a study of the Siemens 7UT86 percentage differential relay as a 60 MVA power transformer protection at the 150 kV Dayeuh Kolot GIS, by taking data to perform mathematical calculations to obtain working parameters and testing. The results of mathematical calculations obtained the rating current value used to select the ratio of installed CT to differential current. The relay is set using slope 1 of 30% and slope 2 of 80% and a differential current of 0.3 I/IrObj to prevent unnecessary blackouts due to the appearance of differential currents by magnetizing currents, inrush, tap changers, CT saturation and as a safety factor. Tests using Omicron test equipment obtained results in the form of actual differential current values of both slope areas, angular stability, current and angular ramping and relay operation delay times. Testing the working parameters of the relay obtained the result that the relay works by commanding the circuit breaker to trip when it exceeds the pick up value. During internal faults and at faults below the pick up value and during external faults the relay standsby.